Diagnostic importance of clinicopathologic features and p16, CD34, MDM2 expression in differential diagnosis of adipocytic tumors - Altun, Eren; Yuksel, Seher; Kaygusuz, Gulsah; Yildiz, Huseyin Yusuf (Acta orthopaedica et traumatologica turcica, 2020)
The aim of this study was to investigate the immunohistochemical stain profiling of adipocytic tumors. From our archive files between the years of 2012-2018, excised, formalin-fixed and paraffin-embedded adipocytic tumors were retrospectively screened and 61 subjects were selected. The gender, age, tumor location and tumor diameter were evaluated. The cases were investigated in terms of p16, CD34, MDM2 expression and clinicopathological information. Of the 61 patients included in the study, we found that 2 had hibernoma, 4 had lipoblastoma, 14 had spindle cell lipoma (SCL), 10 had lipoma, 20 had atypical lipomatous tumor/well differentiated liposarcoma (ALT/WDL), and 11 had dedifferentiated liposarcoma (DDL). In terms of diameter, ALT/WDL and DDL were significantly different from the others (p=0.001, p=0.001, respectively). There was a significant difference between the groups according to the location (p=0.001). 35% (7/20) of ALT/WDLs were in the lower extremities (thighs) and 35% (7/20) were located in the retroperitoneal region. 70% of DDLs (7/11) were located in the retroperitoneum. When CD34 expression was evaluated among the groups, a significant difference was observed (p=0.001). CD34 was positive in 92.9% of SCL cases. p16 immunoreactivity was significantly different between the groups (p=0.001). p16 expression was observed in 50.5% of ALT / WDL cases and 79% of DDL cases. p16 and CD34 expression are valuable in the differential diagnosis of lipomatous tumors when radiological and clinical considerations do not help to differential diagnosis of adipocytic tumors. Level IV, Therapeutic Study.